Harvesting contact-separation-compression vibrations using a flexible and compressible triboelectric generator. (December 2020) - Wardhana, Ede Mehta; Mutsuda, Hidemi; Tanaka, Yoshikazu; Nakashima, Takuji; Kanehira, Taiga; Taniguchi, Naokazu; Maeda, Shuhei; Yonezawa, Takayuki; Yamauchi, Masaaki
Highlights: We propose and develop a polymer-based triboelectric nanogenerator, which is called FC-TENG (a flexible and compressible type of triboelectric nanogenerator), that employs a tribological process for sustainable energy harvesting. The characteristics of the working mechanism of the FC-TENG in the contact, separation, and compression modes are fundamentally elucidated in the vibration test. Abstract: Progress in renewable, portable, and sustainable energy sources for harvesting energy from ambient environments is of great importance in the Internet of Things (IoT) society. Recently, triboelectric nanogenerators (TENGs) have been proposed and developed by many research groups to convert mechanical energy, such as pressure, bending, stretching and vibration, into electrical energy at any given location and time. We must make clear relationships between contact-separation-compression process with external loads and electric performance of triboelectric generators, and should carefully clarify effects of separation-distance and separation-velocity on output voltage, and key parameters for the output voltage in more details. Here, we propose and develop a simple polymer-based flexible and compressible generator that employs a tribological process for sustainable energy such as wind, wave, current, and mechanical vibration. The proposed triboelectric nanogenerator, which is called FC-TENG (a flexible and compressible type of triboelectric nanogenerator), consists of laminated dielectric elastomer sheets and copper films. The characteristics of the working mechanism of the FC-TENG in the contact, separation, and compression modes are fundamentally elucidated in the vibration test, and it is found that the output voltage depends not on the separation distance but the separation velocity. The vertical strain rate of the FC-TENG is a key factor that influences efficient electrical power generation. A suitable initial separation distance must be selected to create a triboelectric potential layer and to achieve high electrical performance. Moreover, a theoretical model is proposed as a design tool, and the resulting average, maximum, and minimum output voltages exhibited good agreement with the experimental data. The proposed FC-TENG could act as a useful device for sustainable energy harvesting.